Gambaran Burnout pada Mahasiswa Keperawatan di Purwokerto - Alimah, Sopiati; Swasti, Keksi Girindra (Jurnal Keperawatan Soedirman, 2016)
ABSTRACTBurnout is physical, emotional, and mental fatigue due to long-term involvement in situations full of emotional demands. Nursing students may be at risk for burnout due to the many tasks and routines of life. This research aimed to describe burnout in students of nursing department and burnout level difference between two periods of intake. This research used quantitative descriptive study with the type of cross sectional design. The sampling technique used total sampling technique. The sample size was 156 respondents. Data were analyzed by using frequency distribution and percentage, as well as Kolmogorov-Smirnov. The majority of respondents were female (80,8%), chose a major that fit their interest (67,9%), very satisfactory GPA (62,8%), and from Central Java (65,4%). The number of respondents in 2013 and 2014 was 77 and 79 students. respectively. The majority of students experiencing moderate level of burnout was (56,4%). Kolmogorov-Smirnov test indicated p-value of 0,170. The majority of students experienced moderate level of burnout and there was no difference of burnout level between 2013 intake and 2014 intake. Keywords: block system, burnout, nursing student ABSTRAKBurnout merupakan kelelahan fisik, emosional, dan mental yang disebabkan keterlibatan jangka panjang dalam situasi yang penuh dengan tuntutan emosional. Mahasiswa keperawatan dapat berisiko mengalami burnout akibat banyaknya tugas dan rutinitas kehidupan yang dilakukan saat menjalani perkuliahan. Penelitian ini bertujuan untuk mengetahui gambaran burnout pada mahasiswa jurusan keperawatan dan perbedaan tingkat burnout antara kedua periode angkatan. Penelitian ini menggunakan metode studi deskriptif kuantitatif dengan desain cross sectional. Sampel dipilih menggunakan teknik total sampling sejumlah 156 responden. Analisis data menggunakan distribusi frekuensi dan persentase, serta Kolmogorov-Smirnov. Mayoritas responden berjenis kelamin perempuan (80,8%), kuliah sesuai dengan minatnya (67,9%), IPK sangat memuaskan (62,8%), dan berasal dari Jawa Tengah (65,4%). Jumlah responden angkatan 2013 dan 2014 adalah 77 dan 79 orang. Mayoritas mahasiswa mengalami burnout tingkat sedang (56,4%). Uji Kolmogorov-Smirnov menunjukkan p-value 0,170. Mayoritas mahasiswa mengalami burnout tingkat sedang dan tidak ada perbedaan tingkat burnout antara angkatan 2013 dan 2014. Kata kunci: burnout, mahasiswa keperawatan, sistem blok.